Pockmarks of the Mediterranean region seas: A Comprehensive Geodatabase for Marine Geomorphological Analysis - Daniele Spatola; Marzia Rovere; Daniele Casalbore; Francesco Latino Chiocci (Scientific Data)
Abstract We present a high-resolution georeferenced database of pockmarks documented on the Mediterranean region seas by using different geophysical technologies (e.g. multibeam, seismic reflection) carried out during oceanographic expeditions. Pockmarks are probably the most ubiquitous morphologies linked to the fluid flow processes at the seafloor with a density up to 3.4 features per km2. They vary from sub-circular to elongated in plan-view and have U- or V-shape in cross section. Through georeferencing over 7,516 pockmarks from the recent literature, we have built an active and systematic database with the aim of incorporating significant data on these seafloor morphologies. The database can have a number of applications: it can be used to assist submarine infrastructure planning (e.g. pipelines, offshore wind farms), ecological study (e.g. pockmarks are habitat for sensitive benthic communities), and natural resource appraisal (e.g. hydrocarbon reservoirs, gas hydrates, offshore groundwater). Moreover, it can serve as a significant tool of scientific investigation, allowing to understand fluid flow processes and marine geosystems.